Collateral effects of COVID-19 stay-at-home orders on violence against women in the United States, January 2019 to December 2020 - Patricia C. Lewis; Yuk Fai Cheong; Nadine J. Kaslow; Kathryn M. Yount (BMC, 2024)
Abstract Background The necessary execution of non-pharmaceutical risk-mitigation (NPRM) strategies to reduce the transmission of COVID-19 has created an unprecedented natural experiment to ascertain whether pandemic-induced social-policy interventions may elevate collateral health risks. Here, we assess the effects on violence against women (VAW) of the duration of NPRM measures that were executed through jurisdictional-level orders in the United States. We expect that stay-at-home orders, by reducing mobility and disrupting non-coresident social ties, are associated with higher incident reporting of VAW. Methods We used aggregate data from the Murder Accountability Project from January 2019 through December 2020, to estimate count models examining the effects of the duration of jurisdictional-level (N = 51) stay-at-home orders on femicide. Additionally, we used data from the National Incident-Based Reporting System to estimate a series of count models that examined the effects of the duration of jurisdictional-level (N = 26) stay-at-home orders on non-lethal violence against women, including five separate measures of intimate partner violence (IPV) and a measure of non-partner sexual violence. Results Results from the count models indicated that femicide was not associated with COVID-19 mitigation strategies when adjusted for seasonal effects. However, we found certain measures of non-lethal VAW to be significantly associated in adjusted models. Specifically, reported physical and economic IPV were positively associated with stay-at-home orders while psychological IPV and non-partner sexual violence were negatively associated with stay-at-home orders. The combination measure of all forms of IPV was positively associated with the duration of stay-at-home orders, indicating a net increase in risk of IPV during lockdowns. Conclusions The benefits of risk-mitigation strategies to reduce the health impacts directly associated with a pandemic should be weighed against their costs with respect to women's heightened exposure to certain forms of violence and the potentially cascading impacts of such exposure on health. The effects of COVID-19 NPRM strategies on IPV risk nationally and its immediate and long-term health sequelae should be studied, with stressors like ongoing pandemic-related economic hardship and substance misuse still unfolding. Findings should inform the development of social policies to mitigate the collateral impacts of crisis-response efforts on the risk of VAW and its cascading sequelae.